HUBUNGAN KADAR VITAMIN D SERUM DENGAN KUALITAS HIDUP PADA PASIEN EPILEPSI - Edith Fitriyana Girsang; Aris Catur Bintoro; Dwi Pudjonarko (NEURONA, 2018)
THE CORRELATION BETWEEN VITAMIN D SERUM LEVELS WITH QUALITY OF LIFE IN EPILEPSY PATIENTABSTRACTIntroduction: Epilepsy affects overall health status and decreases the life quality of epilepsy patient. Seizure frequency, seizure type, daily activity disorder, depression and anxiety also affect the quality of life epilepsy patient. Vitamin D is considered as a neurosteroid modulator of nerve excitability and seizure susceptibility. Studies of vitamin D direct role in epilepsy are limited. Nevertheless, some studies show the role of vitamin D as an anticonvulsant that reduces the incidence of seizures.Aim: To determine the correlation between vitamin D serum levels with quality of life in epilepsy patient.Method: A cross sectional observational study on people with epilepsy in neurology clinic at Dr. Soeselo Hospital, Slawi, Dr Kariadi Hospital, and Tugurejo Hospital, Semarang in July 2017-January 2018. The quality of life was assessed with Quality of Life in Epilepsy 31 (QOLIE-31). Vitamin D serum levels measured using enzyme-linked immunosorbent assay (ELISA) method. Data were analyzed using Spearman test. Results were considered significant if p<0.05.Results: There was no correlation between vitamin D serum levels with quality of life in epilepsy. There was significant correlation between anxiety with quality of life and there were difference between age group with quality of life. Discussion: There was no correlation between serum vitamin D levels and  quality of life in epilepsy patient.Keywords: Epilepsy,quality of life epilepsy, vitamin DABSTRAKPendahuluan: Epilepsi mempengaruhi status kesehatan secara keseluruhan dan menurunkan kualitas hidup pasien epilepsi. Frekuensi bangkitan, tipe bangkitan, gangguan aktivitas harian, depresi dan ansietas, juga memengaruhi kualitas hidup pasien epilepsi. Vitamin D dianggap neurosteroid, sebagai modulator eksitabilitas saraf dan kerentanan bangkitan. Bukti langsung untuk peran vitamin D dalam epilepsi terbatas. Namun beberapa penelitian menunjukkan peran vitamin D sebagai antikonvulsan yang mengurangi kejadian bangkitan.Tujuan: Mengetahui hubungan kadar vitamin D serum dengan kualitas hidup pada pasien epilepsi.Metode: Penelitian potong lintang terhadap pasien epilepsi yang berobat ke Poliklinik Saraf RSUD Dr. Soeselo, Slawi, RSUP Dr. Kariadi, Semarang, dan RS Tugurejo, Semarang pada bulan Juli 2017-Januari 2018. Kualitas hidup dinilai menggunakan kuesioner Quality of Life in Epilepsy 31 (QOLIE-31), pengukuran kadar vitamin D serum menggunakan metode enzyme-linked immunosorbent assay (ELISA). Data dianalisis dengan uji Spearman, hasil dianggap bermakna jika p<0,05.Hasil: Tidak didapatkan hubungan antara kadar vitamin D serum dengan kualitas hidup serta domainnya pada pasien epilepsi. Didapatkan hubungan yang bermakna antara ansietas dengan kualitas hidup dan antara kelompok usia dengan kualitas hidup.Diskusi: Tidak terdapat hubungan bermakna antara kadar vitamin D serum dengan kualitas hidup pada pasien epilepsi.Kata kunci: Epilepsi, kualitas hidup, vitamin D